The strategic evolution of Aer Lingus from a full-service airline to a low-cost carrier and finally positioning itself into a value hybrid airline - O'Connell, John F.; Connolly, David (Tourism Economics, 2016)
Aer Lingus has been an unique airline as it transitioned from a full-service airline to a low-cost carrier and is currently positioned as a value hybrid airline. It has coexisted with Ryanair for decades and it encountered three imminent periods where bankruptcy prevailed from 1993 to 2009. The research aims to uncover the various strategies that were applied to structurally re-engineer the carrier in order to adapt to its evolving competitive landscape. The key pillars underpinning Aer Lingus’ turnaround as a value hybrid were as follows: strict adherence to capacity discipline; relentless cost control and value-adding, consumer-driven product differentiation; innovative partnerships including contract flying to alleviate its problematic seasonality issues inherent in Aer Lingus markets; and by re-engineering its Dublin-based hub airport. A visionary master plan for the hub was fabricated to capitalize on Ireland’s geographical positioning which targeted the traffic flows between UK/European and North American destinations through its synchronized connection network at Dublin.